An insight in Omicron variant and the effectiveness of available vaccines for COVID-19 - Dr. Bedanta Roy, Kee Kah Wei, (Pakistan Journal of Medical & Health Sciences, 2023)
The Omicron variant (B.1.1.529) recently emerged from South Africa is declared as Variant of Concern (VOCs). More than 30 mutations in the spike proteins were detected, which weaponized the variant with higher transmission rates, a greater affinity for viral binding, and significant antibody escape. COVID-19 vaccines may provide an increase in protection against Omicron by producing more significant levels of neutralising antibodies, still comprehensive clinical data is required. MeSH words: COVID-19, Omicron, vaccine